2018
DOI: 10.1093/glycob/cwy020
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated fucans and a sulfated galactan from sea urchins as potent inhibitors of selectin-dependent hematogenous metastasis

Abstract: Metastasis is responsible for the majority of cancer-associated deaths, though only a very small number of tumor cells are able to efficiently complete all the steps of that process. Tumor cell survival in the bloodstream is one of the limiting aspects of the metastatic cascade. The formation of tumor cell-platelet complexes that promote tumor cell survival is facilitated by the binding of P-selectin on activated platelets to sialyl Lewis-containing oligosaccharides on the surface of tumor cells. Inhibition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In this framework, the specific biotechnological potential of the regular structure of echinoid fucoidans remains poorly investigated. However, it was shown that sulphated polysaccharides isolated from three sea urchin species have different anticoagulant and anti-selectin activities, which give them a potential activity in the attenuation of metastasis progression [245,246].…”
Section: Bioactive Moleculesmentioning
confidence: 99%
“…In this framework, the specific biotechnological potential of the regular structure of echinoid fucoidans remains poorly investigated. However, it was shown that sulphated polysaccharides isolated from three sea urchin species have different anticoagulant and anti-selectin activities, which give them a potential activity in the attenuation of metastasis progression [245,246].…”
Section: Bioactive Moleculesmentioning
confidence: 99%
“…In conclusion, although the potential anti-cancer compounds obtained from echinoderms have been widely illustrated in the literature [49], the contribution of sea urchins to this field of research is still very limited and is represented only by a few pilot studies previously published and which focused on steroidal and polysaccharidic constituents [4,50,51]. Here, we have demonstrated the cytotoxicity of extracts from A. lixula's cell-free CF towards TNBC cells in vitro.…”
Section: Discussionmentioning
confidence: 66%
“…Sea urchins are invertebrates belonging to the class Echinoidea (phylum Echinodermata), which incorporates more than 700 described extant species worldwide. Recently, they have been the object of growing interest as available sources of new biomolecules which, on the basis of their activity as antibacterial, antiviral, antiprotozoal, antifungal, and anticancer agents, may be potential candidates for drug discovery and development [1][2][3][4]. Indeed, these animals have developed complex molecular mechanisms to use in various biological processes, such as communication, defense, reproduction, and antimicrobial resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Their study revealed that Ups-fucoidan inhibited growth by downregulating VEGFC/VEGFR3, c-MET, cyclin D1, CDK4, PI3K/Akt and ERK, and suppressed adhesion and invasion by downregulating L-selectin and upregulating TIMPs. Similarly, other sulfated polysaccharides isolated from marine invertebrates (Strongylocentrotus droebachiensis and Echinometra lucunter) were revealed to attenuate tumor metastasis by a P-selectin-mediated mechanism (39). Another study (40) also demonstrated that Undaria pinnatifida fucoidan significantly inhibited the hypoxia-induced expression, nuclear translocation and activation of HIF-1α, the synthesis and secretion of VEGF-C and HGF, as well as the invasion and lymphatic metastasis in a mouse hepatocarcinoma Hca-F cell line.…”
Section: Discussionmentioning
confidence: 94%